Analysis of the Role of Shopee Live and Digital Marketing Strategy in Optimizing Sales at CV Kampung Souvenir - Joko Purnomo, Kurniawan; Ardhi Putra, Ida Bagus; Gladysia Sistadanta , Dewa Ayu (CV. Publikasi Indonesia, 2025)
In the digital era, consumer shopping patterns continue to evolve, and one rapidly growing trend is live shopping through platforms such as Shopee Live. This study aims to understand how Shopee Live can help enhance customer engagement and support sales at CV Kampung Souvenir. Additionally, the research will explore the most effective digital marketing strategies for the company to implement. Data will be collected through interviews with the company’s internal team, customer surveys, and sales trend analysis. This research is expected to provide valuable insights for CV Kampung Souvenir and other MSMEs in leveraging digital technology to grow their businesses amid increasingly fierce competition in the online market.